Tuberculosis Screening of New Hospital Employees: Compliance, Clearance to Work Time, and Cost Using Tuberculin Skin Test and Interferon-Gamma Release Assays. (November 2014) - Foster-Chang, Sarah A.; Manning, Mary L.; Chandler, Laura
Selection of the most suitable test(s) for detection of Mycobacterium tuberculosis (TB) infection should be based on purpose, setting, effectiveness, and cost. Two tests are available to screen for latent TB: the tuberculin skin test (TST) and the more recent interferon-gamma release assays (IGRAs). Based on the administrative, logistic, and technical ease of use, an IGRA trial was initiated by the occupational health department at an urban Veteran's Administration health care facility for TB screening of new employees. As a result, new employees completing the pre-placement process within the organization's designated 14 days increased from 77% to 97%, new employee clearance to work time decreased from 13.18 to 5.91 days, and new employee TB screening costs were reduced by 40%. The IGRA is an acceptable alternative to the TST and has significant potential to improve the process of pre-placement TB screening.